Attitudes to Medication after Kidney Transplantation and Their Association with Medication Adherence and Graft Survival: A 2-Year Follow-Up Study - Mirjam Tielen; Job van Exel; Mirjam Laging; Denise K. Beck; Roshni Khemai; Teun van Gelder; Michiel G. H. Betjes; Willem Weimar; Emma K. Massey (Journal of Transplantation)
Background. Nonadherence to medication is a common problem after kidney transplantation. The aim of this study was to explore attitudes towards medication, adherence, and the relationship with clinical outcomes. Method. Kidney recipients participated in a Q-methodological study 6 weeks after transplantation. As a measure of medication adherence, respondents completed the Basel Assessment of Adherence to Immunosuppressive Medications Scale (BAASIS©-interview). Moreover, the intrapatient variability in the pharmacokinetics of tacrolimus was calculated, which measures stability of drug intake. Data on graft survival was retrieved from patient records up to 2 years after transplantation. Results. 113 renal transplant recipients (19–75 years old) participated in the study. Results revealed three attitudes towards medication adherence—attitude 1: “confident and accurate,” attitude 2: “concerned and vigilant,” and attitude 3: “appearance oriented and assertive.” We found association of attitudes with intrapatient variability in pharmacokinetics of tacrolimus, but not with self-reported nonadherence or graft survival. However, self-reported nonadherence immediately after transplantation was associated with lower two-year graft survival. Conclusion. These preliminary findings suggest that nonadherence shortly after kidney transplantation may be a risk factor for lower graft survival in the years to follow. The attitudes to medication were not a risk factor.